Development of Sharia Finance Digitalization Towards Inclusive Finance Within a Sharia Maqashid Framework (Case Study on PT Bank Syariah Indonesia’s BSI Mobile Banking Product) - Angel Dwi Satria; Anita Anita; Krismadayanti Krismadayanti; Heni Noviarita (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2021)
The level of Islamic financial literacy and inclusion in Indonesia is still relatively low, data from the Financial Services Authority (OJK) in 2020 shows that the level of Islamic financial literacy is around 8.93% compared to the national index of 76.19% and the level of Islamic financial inclusion is around 9.9%. has not reached 10%. This low public access can be overcome by combining financial services and products with the latest technology. This is an opportunity for the Islamic finance industry to innovate digitally. The author examines digital product innovation to increase literacy and inclusion of Islamic finance, namely the